Revisit Intention in Trend Driven Casual Dining: A Stimulus-Organism-Response Approach in Trendy Noodle Restaurants - Helmi Aditya Reza Gunawan; Rizqa Amelia Zunaidi; Norma Septin Nurlaela; Talia Rahmanina Az Zahra; Rahaditya Dimas Prihadianto (LPPM Telkom University Surabaya, 2026)
As trendy noodle restaurants continue to proliferate in Indonesia, competition in this industry has become increasingly fierce, making it all the more important to understand the factors that drive customer satisfaction and the intention to return. This study focuses on modern casual dining restaurants characterized by customizable noodle menus, distinctive food presentation, and a socially oriented dining experience.Using the Stimulus-Organism-Response (SOR) model, this study examines three external stimuli (price, food quality, and restaurant ambiance) and their influence on customer satisfaction (organism) and intention to revisit (response). A quantitative research design employing Covariance-Based Structural Equation Modeling (CB-SEM) was used, with data collected from 243 respondents who had previously dined at trendy noodle restaurants in Indonesia. The results indicate that food quality is the strongest predictor of customer satisfaction, while restaurant ambiance and customer satisfaction are significant predictors of revisit intention. Interestingly, price had no significant effect on either customer satisfaction or intention to revisit, indicating that customers of trendy casual restaurants are more sensitive to quality and experience than to price. These results suggest that in an experience-oriented dining environment, customers prioritize food quality and atmosphere over price.